Management of Dystocia Due to Unilateral Post-Cervical Torsion in Ewe - Parmar, Kirankumar; Hardikbhai, Jakotra; Rajeshbhai, Vala (The Indian Journal of Animal Reproduction, 2025)
The present clinical case of unilateral post-cervical torsion in ewe reports the successful delivery of a fetus by rolling the ewe using Schaffer’s method with little modification from large animals. A pluriparous non-descript ewe aged about 2.5 years was presented at VCC, Junagadh, Gujarat with a history of completion of gestation and straining for 24 hours. The per-vaginal fetus was delivered successfully after rolling the dam with slight traction. The dam had an uneventful recovery.
Keywords: Torsion; Dystocia; Schaffer’s Method; Ewe